2013
DOI: 10.1177/1535370213477976
|View full text |Cite
|
Sign up to set email alerts
|

A high-fat diet increases interleukin-3 and granulocyte colony-stimulating factor production by bone marrow cells and triggers bone marrow hyperplasia and neutrophilia in wistar rats

Abstract: It is well established that the excessive consumption of a high-fat diet (HFD) results in overweight, obesity and an increase in leptin concentrations, which triggers a chronic inflammatory condition that is associated with a high white blood cell count. Two-month-old male Wistar rats were fed a control (CON) diet or an HFD for 12 weeks. After this period, hemogram, myelogram and biochemical parameters were evaluated along with the cell cycle and the percentage of CD34(+) cells in the bone marrow as well as ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…Both rapid dysregulation of B-cell populations that results from diminished cellular differentiation [61] and enhancement of hematopoiesis and lymphopoiesis [62] are reported, but these studies differ by the diet protocol. Consistent with data on ob/ob mice, leukocytosis and neutrophilia have also been described in HFD-rodents together with a granulopoiesis in the BM due to an increase in G-CSF production by stromal cells [60,63,64].…”
Section: Metabolic Disorders and Bone Marrow Hematopoiesissupporting
confidence: 75%
“…Both rapid dysregulation of B-cell populations that results from diminished cellular differentiation [61] and enhancement of hematopoiesis and lymphopoiesis [62] are reported, but these studies differ by the diet protocol. Consistent with data on ob/ob mice, leukocytosis and neutrophilia have also been described in HFD-rodents together with a granulopoiesis in the BM due to an increase in G-CSF production by stromal cells [60,63,64].…”
Section: Metabolic Disorders and Bone Marrow Hematopoiesissupporting
confidence: 75%
“…Male Wistar rats fed an HFD for 12 weeks. exhibited leukocytosis and neutrophilia with increased CRP, leptin, cholesterol and TG concentrations [8]. In addition, the HFD bone marrow cells had a higher capacity to proliferate and differentiate into granulocytic cells which produce IL-3.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that an HFD induced central and peripheral high leukocyte count and circulating neutrophils levels in rats [8]. The HFD animals had a higher number of bone marrow cells, which had a greater capacity to produce IL-3 and G-CSF [8]. It appears that HFD has an indirect effect on the levels of IL-3.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…One possible mechanism postulated to explain the augment in granulopoiesis is an increased production of G-CSF by bone marrow cells in the obese group compared to controls 23 . Moreover, mesenchymal stem cells (MSC) of HFD rats express considerably higher amounts of nuclear Factor kappa β (NF-kβ) as well as tumor necrosis factor alpha (TNFα), IL-1 and IL-6, which can inhibit adipocyte differentiation of MSC thus shifting bone marrow differentiation towards osteoblasts.…”
Section: Obesity and Chronic Inflammation And The Hematopoietic Systemmentioning
confidence: 99%